Genome Wide Analysis Reveals Host Genetic Variants that Associate with Reduction in Clostridium difficile Infection Recurrence (rCDI) in Patients Treated with Bezlotoxumab. (4th October 2017) - Shaw, Peter; Shen, Judong; Dorr, Mary Beth; Wilcox, Mark; Li, Junhua; Mogg, Robin; Mehrotra, Devan V; Blanchard, Rebecca L
Abstract: Background: Bezlotoxumab (BEZ) and actoxumab (ACT) are monoclonal antibodies against C. difficile toxins B and A, respectively. Patients receiving a single infusion of BEZ alone or with ACT in the MODIFY I/II trials showed a consistent reduction in the rate of rCDI over a 12-week period compared with a placebo (PBO) infusion. Exploratory genome wide analyses were conducted to determine whether genetic variants across the genome were associated with treatment response (rCDI). Methods: DNA was extracted from blood obtained from patients who consented to genetic analysis (PGx population). Genetic data were generated on a commercial Axiom array platform (Affymetrix). Genotype imputation was performed using the 1000 Genomes Phase 3 reference data and Impute2 software after genetic quality control. Data from BEZ and ACT+BEZ arms were combined to provide increased power. The logistic regression with likelihood ratio test was used to search for single nucleotide polymorphisms (SNPs) that were strongly associated with a treatment effect on rCDI. Results: An SNP rs2516513 located in the extended major histocompatibility complex (xMHC), region with a minor allele frequency of 25% in the general population, was associated with rCDI ( P = 3.04E-08) (Figure 1). rCDI rates for the PGx population and in subgroups at high/low risk for rCDI stratified by SNP rs2516513 are shown in Table 1. Carriers of the T allele of SNP rs2516513 were associated with a statistically significant reduction in rCDI in BEZ-treated patients but not in PBO-treated patients (DrCDI = -21.5%). The magnitude of the effect of the T allele on rCDI is most prominent in patients who have ≥1 risk factor for rCDI (DrCDI = -24.6%), but is also present in patients without risk factors (DrCDI = -10.6%). In CC homozygous patients, rCDI rates are similar in both treatment groups and in patients at high and low risk of rCDI. Conclusion: An SNP variant rs2516513 is associated with a lower rate of rCDI recurrence in patients treated with BEZ. The location of the associated genetic variant on chromosome 6 within xMHC, suggests that a host driven, immunological mechanism may play a role in rCDI and may predict patients most likely to respond to BEZ. As this is an exploratory finding, the results should be replicated in an independent validation study. Disclosures: P. Shaw, Merck & Co., Inc.: Employee, May own stock/hold stock options in Company; J. Shen, Merck & Co., Inc.: Employee, may hold stock/hold stock options in the Company; M. B. Dorr, Merck & Co., Inc.: Employee and Shareholder, may own stock/hold stock options in the Company; J. Li, BGI-Shenzhen: Employee, Salary; R. Mogg, Merck & Co., Inc.: Employee, May hold stock/stock options in the Company; D. V. Mehrotra, Merck & Co., Inc.: Employee, may own stock/hold stock options in the Company; R. L. Blanchard, Merck & Co., Inc.: Employee, may own stock/hold stock options in the Company